Performance of Soybean Under Different Levels of Phosphorus and Potassium (Bangladesh Agronomy Journal, 2016)
A field experiment was conducted at the Sher-e-Bangla Agricultural University Farm, Dhaka, Bangladesh during December 2013 to April 2014 to evaluate the effect of phosphorus (P0: 0 kg TSP ha-1, P1: 100 kg TSP ha-1, P2: 175 kg TSP ha-1, P3: 250 kg TSP ha-1) and potassium (K0: 0 kg MoP, K1: 60 kg MoP ha-1, K2: 120 kg MoP ha-1, K3: 180 kg MoP ha-1), and their combinations on growth and yield of soybean (Glycine max). Number of nodules plant-1, number of filled pods plant-1, number of seeds pod-1, 1000-seed weight, seed yield, biological yield and harvest index increased significantly up to 175 kg ha-1 TSP. On the other hand, numbers of nodules plant-1, number of filled pods plant-1, length of pod, number of seeds pod-1, 1000-seed weight, seed yield, stover yield and biological yield were enhanced significantly up to 120 kg ha-1 MoP. The treatment of combined phosphorus @ 175 kg ha-1 and potassium @ 120 kg MoP ha-1 depicted the highest number of filled pods plant-1 (63.00), length of pod (3.16 cm), number of seeds pod-1 (3.11) vis a vis the highest (3.67 t ha-1) seed yield. Thus, the combined application of 175 kg ha-1 TSP and 120 kg ha-1 MoP could be the optimum for getting maximum yield of soybean.Bangladesh Agron. J. 2016, 19(1): 99-108